Sukuk pada Blockchain: Aplikasi, Keunggulan dan Tantangannya - Nurul Izzati Septiana; Hilda Sanjayawati (Universitas Islam Raden Rahmat, 2021)
This paper aims to identify key insights from the available literature review on blockchain in the sukuk market and provide a commentary of its prospects specifically in its application within the sukuk market advantages and challenges. The paper primarily applies a qualitative approach and literature review as a research method. The result showed that smart sukuk has the potential of becoming the future for sukuk issuances and may contribute to the spread of sukuk more widely, leading to the expansion of Islamic funding. The advantages of smart contracts could facilitate transactions in convenient way and hence would contribute to wellbeing of the ummah, thus achieving the maslaha. The use of smart contracts designed to protect against fraud is also consistent with maqasid al-Shariah (purposes of Shariah), which is the protection of al-mal (property).